1991
DOI: 10.1101/gad.5.3.496
|View full text |Cite
|
Sign up to set email alerts
|

Promoter analysis of genes that are coordinately expressed during pollen development reveals pollen-specific enhancer sequences and shared regulatory elements.

Abstract: We have investigated the functional organization and properties of cis regulatory elements in the promoter regions of two genes from tomato (LAT52 and LAT59) that are preferentially and coordinately expressed during pollen maturation. Promoter deletion analysis in transgenic plants demonstrated that only minimal (~200 bp) promoter proximal regions are required for developmentally regulated expression in pollen and in specific cell types of the sporophyte. Cis-acting regulatory regions of these two promoters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
220
1
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(225 citation statements)
references
References 26 publications
3
220
1
1
Order By: Relevance
“…2). However, this sequence differs slightly from those previously identified (Twell et al, 1991;Weterings et al, 1995;Bate and Twell, 1998; TGTTGGTT instead of TGTGGTT). One sugar-repressive box (Morita et al, 1998) has also been found in this promoter (Fig.…”
contrasting
confidence: 70%
See 3 more Smart Citations
“…2). However, this sequence differs slightly from those previously identified (Twell et al, 1991;Weterings et al, 1995;Bate and Twell, 1998; TGTTGGTT instead of TGTGGTT). One sugar-repressive box (Morita et al, 1998) has also been found in this promoter (Fig.…”
contrasting
confidence: 70%
“…However, digital northern analysis carried out with Genevestigator (Zimmermann et al, 2004; https:// www.genevestigator.ethz.ch) did not reveal any potential regulation by auxin. One pollen box is present (Twell et al, 1991), as well as two dark induction or light repression boxes (Dehesh et al, 1990;Inaba et al, 2000;Fig. 2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although others have found such transient assays to be reliable methods to measure gene activities, we have relied on the data obtained from the analyses of transgenic plants to study the isocitrate lyase 5' flanking region because of the potential problems in interpreting the results of the bombardment experiments (Klein et al, 1988(Klein et al, , 1989Bruce et al, 1989;Goff et al, 1990;Rolfe and Tobin, 1991;Twell et al, 1991).…”
Section: Comparison Of Promoter Activities In a Transient Expression mentioning
confidence: 99%